2022
DOI: 10.3389/fpsyt.2022.914897
|View full text |Cite
|
Sign up to set email alerts
|

Altered Interoceptive Sensibility in Adults With Chronic Tic Disorder

Abstract: BackgroundInteroception refers to the sensing, interpretation, integration, and regulation of signals about the body’s internal physiological state. Interoceptive sensibility is the subjective evaluation of interoceptive experience, as assessed by self-report measures, and is abnormal in numerous neuropsychiatric disorders. Research examining interoceptive sensibility in individuals with chronic tic disorders (CTDs), however, has yielded conflicting results, likely due to methodologic differences between studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 123 publications
(226 reference statements)
1
5
0
Order By: Relevance
“…Across all three groups, SH was associated with OCD and attention deficit hyperactivity disorder (ADHD) symptoms but not with tic severity. The second report investigated interoception in adults with or without CTD using a published self-report measure ( Narapareddy et al . 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Across all three groups, SH was associated with OCD and attention deficit hyperactivity disorder (ADHD) symptoms but not with tic severity. The second report investigated interoception in adults with or without CTD using a published self-report measure ( Narapareddy et al . 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Section 1, we claimed that TS is marked by hyperprecision weighting over (the likelihood of) interoceptive sensory data. This is strongly consonant with the findings of Rae et al (2019b), who found that participants with TS had an objectively lower interoceptive accuracy on a heartbeat tracking task, as well as an increased (self-reported) sensitivity to interoceptive signals (cf., Ganos et al, 2015;Narapareddy et al, 2022). However, these researchers did not investigate the mechanism underlying tics and the subsequent attenuation of the premonitory sensation.…”
Section: Empirical Predictions Limitations and Future Directionsmentioning
confidence: 99%
“…with greater premonitory urge severity [20]. Uaeda et al theorize that premonitory urge phenomena in TS may represent enhanced or aberrant interoceptive sensations [21].…”
Section: Key Pointsmentioning
confidence: 99%
“…Some research suggests that dimensions of interoception have been found to predict premonitory urges and tic severity among individuals with TS [18], whereas other sources contend that interoceptive sensitivity is an independent, but clinically relevant, construct among populations with TS [19]. Relative to healthy adults, adults with TS experience greater general body awareness and anxiety-associated somatization [20]. Furthermore, evidence suggests that greater body awareness is significantly associated with greater premonitory urge severity [20].…”
Section: Phenomenology Of Tourette Syndromementioning
confidence: 99%
See 1 more Smart Citation